OPTIMIZATION OF DECISION SUPPORT SYSTEM (DSS) CUSTOMER SERVICE OF TELECOMMUNICATION COMPANIES WITH MOORA METHOD - Sari, Dely Indah; Sondra Wijaya, I Made; Harahap, Widiya Lestari; Rizki, Mohd. (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2025)
Abstract: Decision Support System (DSS) in telekomunication company service is the key to improving customer satisfaction and operational efficiency. This study aims to assess and select the optional customer service strategy using the Mutly Objective Optimization on The Basic of Ratio Analysis (MOORA) method. This approach is used to analyze various indicators such as respon time, complaint resolution, service cost and costomer satisfaction to find the most efficient solution. The research finding indicate that the MOORA method can provide from the calculation results, it was found that the age range <25 years was ranked first as users who felt satisfied with Product Quality, Price, Service Quality, and the most telecommunications users and the second rank was the age range 25-35 years, the third rank was the age range 36-45 years, the fourth rank was the age range >45 years. The implementation of DSS strengthened by MOORA is expected to improve the quality of service and competitiveness of companies in the competitive telecomunication industry. Keywords: customer service; DSS; MOORA; telecomunication; optimization  Abstrak: Sistem Pendukung Keputusan (DSS) dalam layanan perusahaan telekomunikasi merupakan kunci untuk meningkatkan kepuasan pelanggan dan efisiensi operasional. Penelitian ini bertujuan untuk menilai dan memilih strategi layanan pelanggan opsional dengan menggunakan metode Mutly Objective Optimization on The Basic of Ratio Analysis (MOORA). Pendekatan ini digunakan untuk menganalisis berbagai indikator seperti waktu respons, penyelesaian keluhan, biaya layanan dan kepuasan pelanggan untuk menemukan solusi yang paling efisien. Temuan penelitian menunjukkan bahwa metode MOORA dapat memberikan Dari hasil perhitungan, ditemukan bahwa rentang usia <25 tahun menduduki peringkat pertama sebagai pengguna yang merasa puas terhadap Kualitas Produk, Harga, Kualitas Layanan, dan pengguna telekomunikasi terbanyak dan peringkat kedua adalah rentang usia 25-35 tahun, peringkat ketiga adalah rentang usia 36-45 tahun, peringkat keempat adalah rentang usia >45 tahun. Penerapan DSS yang diperkuat oleh MOORA diharapkan dapat meningkatkan kualitas layanan dan daya saing perusahaan dalam industri telekomunikasi yang kompetitif. Kata kunci: DSS; MOORA; layanan pelanggan; telekomunikasi; optimasi